Prenatal alcohol and tetrahydrocannabinol exposure: Effects on spatial and working memory - Lei, Annie; Breit, Kristen R.; Thomas, Jennifer D. (Frontiers in Neuroscience, 2023)
Introduction Alcohol and cannabis are widely used recreational drugs that can negatively impact fetal development, leading to cognitive impairments. However, these drugs may be used simultaneously and the effects of combined exposure during the prenatal period are not well understood. Thus, this study used an animal model to investigate the effects of prenatal exposure to ethanol (EtOH), Δ-9-tetrahydrocannabinol (THC), or the combination on spatial and working memory. Methods Pregnant Sprague–Dawley rats were exposed to vaporized ethanol (EtOH; 68 ml/h), THC (100 mg/ml), the combination, or vehicle control during gestational days 5–20. Adolescent male and female offspring were evaluated using the Morris water maze task to assess spatial and working memory. Results Prenatal THC exposure impaired spatial learning and memory in female offspring, whereas prenatal EtOH exposure impaired working memory. The combination of THC and EtOH did not exacerbate the effects of either EtOH or THC, although subjects exposed to the combination were less thigmotaxic, which might represent an increase in risk-taking behavior. Discussion Our results highlight the differential effects of prenatal exposure to THC and EtOH on cognitive and emotional development, with substance- and sex-specific patterns. These findings highlight the potential harm of THC and EtOH on fetal development and support public health policies aimed at reducing cannabis and alcohol use during pregnancy.